Brief historical review of whaling - Y. A. Mikhalev (Ukrainian Antarctic Journal, 2009)
Special characteristics of whaling given beginning from old historical times. Distinguished different periods of this industry. Explained the transfer of whaling into the Antarctic. Given the catch data of main whaling species. The history of creation of International Convention on regulation of whaling and development of unified rules of whaling. Described the characteristics of whaling at current times.